2020
DOI: 10.1177/0885328220914407
|View full text |Cite
|
Sign up to set email alerts
|

Combination of an allogenic and a xenogenic bone substitute material with injectable platelet-rich fibrin – A comparative in vitro study

Abstract: The aim of the in vitro study was a comparison of an allogenic (ABSM) and a xenogenic bone substitute material (XBSM) with and without injectable platelet-rich fibrin (ABSM-i-PRF & XBSM-i-PRF) on cell characteristics of human osteoblasts (HOB). Here, ABSM and XBSM (+ i-PRF = test; - i-PRF = control) were incubated with HOB for 3, 7 and 10 days. HOB viability, migration, proliferation and differentiation (RT-PCR on alkaline phosphatase (AP), bone morphogenetic protein 2 (BMP-2) and osteonectin (OCN)) were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 59 publications
(87 reference statements)
0
46
0
Order By: Relevance
“…Although biochemical signals are released from i-PRF, their effects on cells are limited and, surprisingly, not concentration-dependant [ 21 ]. Several studies found a wide range of biocompatibility using 20‒100% conditioned media from i-PRF on human fibroblasts [ 17 ] and osteoblasts [ 8 , 21 , 22 ]. Optimal cell viability also varied over 1‒5 d [ 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although biochemical signals are released from i-PRF, their effects on cells are limited and, surprisingly, not concentration-dependant [ 21 ]. Several studies found a wide range of biocompatibility using 20‒100% conditioned media from i-PRF on human fibroblasts [ 17 ] and osteoblasts [ 8 , 21 , 22 ]. Optimal cell viability also varied over 1‒5 d [ 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians use i-PRF in combination with particulate bone grafts to promote the biological and physical properties of the materials [ 8 ]. The combination has shown benefits, such as improved angiogenesis and handling ability by combining the small bone granules into a bulk material to use in bone grafting surgery [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The porcine-derived type I and III collagen membrane has a bilayer structure, consisting of a compact outer layer and a porous inner layer of collagen fiber bundles [10]. Both materials, alone and in combination by means of GBR-procedures, are frequently used in preclinical as well as clinical regenerative maxillofacial surgery [3,18,[30][31][32].…”
Section: Study Materialsmentioning
confidence: 99%
“…Tissue engineering in the maxillofacial region aims for regeneration of soft and hard tissue deficiencies in order to sustain oral-related health as well as to improve masticatory function. As autograft harvesting results in increased local morbidity, allogeneic, alloplastic, and xenogeneic grafts are frequently used, even though autogenous tissue remains the biological gold standard [ 1 , 2 , 3 ]. Most studies in biomaterial research mainly focus on the mechanical and functional properties of the material [ 4 ].…”
Section: Introductionmentioning
confidence: 99%